PENGARUH KEBIJAKAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN JNE CABANG BANDUNG - Widiastuti, Reza; Sari, Zufita; Bisri, Tati S. (STIBANKS Al Ma'soem Bandung, 2018)
This study aims to analyze the influence of pricing policy on consumer purchasing decisions at the Bandung Branch of JNE. Data analysis used is normality test and proved again by Kolgomorov, simple linear, t test, and detemination coefficient. Based on the results of research that has been carried out the influence of pricing policies on consumer purchasing decisions JNE Bandung Branch has normal data, simple linear equations Y = 27,936 + 0,575 X with a positive constant, it can be interpreted if the independent value is assumed to be constant, then the dependent value will rise. Test of the determination coefficient Adjusted R Square is a R2 value that is adjusted so that the image is closer to the quality of the model exploration, from the calculation of the Adjusted R Square value of 21.1%. This means that 21.1% of Consumer Purchasing Decisions are influenced by the independent variable Price Determination Policy. While the remaining 78.9% is influenced by factors that are not observed. Then based on the Partial Test (t test) there is a test result on the regression coefficient with tcount can tcount of 5.241> t table 1.660, then the Pricing Policy affects the Consumer Purchase Decision which means that if the company is wiser in determining the price it will be followed up Consumer Purchasing Decisions. Thus the Price Determination Policy affects the purchasing decisions of the JNE Branch of Bandung Consumer.